The relationship of correct option location, distractor efficiency, difficulty and discrimination indices in analysis of high-stakes multiple-choice questions exam of medical students - Shafiayan, Madjid; Izanloo, Balal (Revista de la Universidad del Zulia, 2019)
Background: Analysis of Multiple-Choice Questions (MCQs) is the psychometric method pertains to validity and reliability of the exam. Objective: This study was conducted to identify psychometric properties of high-stakes MCQ exam of under-graduate Medical Students' assessment. With this in mind we tried to investigate the effect of correct option location on difficulty index (DIF I) and discrimination index (DI) regarding distractor efficiency (DE) in the context of Medical Education. Materials and Methods: National high –stake MCQ exam was conducted to senior medical students belonging to universities of Medical Sciences to assess knowledge of Basic and Clinical sciences. Data were analyzed using Classical Test Theory to investigate effect of correct – option position on DIF I and DI and DE. Microsoft Excel spread sheet; SPSS version 23; R Psych Package softwars were used. Descriptive statistics; Point biserial correlation; Fisher's Exact Test; ANOVA test and Pearson correlation were performed. Results: The mean score was 107.30±19.10 ranging from 40 – 174.Mean DIF I and DI were 0.54 ± 0.20 and 0.20 ± 0.10, respectively. Fourthly three and half percent MCQs were of average DIF I (0.30˂ P˂ 0.70) and DI ˃0.2. Overall 127/600 (21.16%) were null distractors (˂ 5%) and DE was 78.84%. Mean DIF I and SD key option 1; 2; 3; 4 were 0.50±0.20; 0.59 ± 0.18; 0.54 ± 0.23; 0.50 ± 0.17, respectively. Conclusion: Our data suggest that correct option location remarkably affect DIF I of item. We believe our study provides considerable insight into validating MCQs of Medical students' assessment to optimizing question bank